2018
DOI: 10.12659/pjr.902417
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Diagnosis of Chronic Encapsulated Intracerebral Hematoma, a Comparison of Computed Tomography (CT) and Magnetic Resonance Imaging (MRI) characteristics

Abstract: SummaryBackgroundChronic encapsulated intracerebral hematoma (CEICH) is a rare type of intracerebral hematoma that is often misdiagnosed.To explore the characteristics of CEICH on computerized tomography (CT) and magnetic resonance imaging (MRI).Material/MethodsClinical, CT, MRI, and susceptibility weighted imaging (SWI) data of 5 patients who were diagnosed with CEICH on surgery and pathology were retrospectively analyzed.ResultsCT showed quasi-circular or elliptical lesions with clear borders in all 5 cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…The intracapsular bleeding showed varying degrees of T1 and T2 hyperintensity depending on chronicity. The study suggested that ring enhancement with intracapsular bleeding on MRI can be helpful in the diagnosis of CEIH [17].…”
Section: Discussionmentioning
confidence: 90%
“…The intracapsular bleeding showed varying degrees of T1 and T2 hyperintensity depending on chronicity. The study suggested that ring enhancement with intracapsular bleeding on MRI can be helpful in the diagnosis of CEIH [17].…”
Section: Discussionmentioning
confidence: 90%
“…Remarkably, with 62% of the cases, more than half of cSDH showed mass-like contrast enhancement, a finding that was also reported in 3 of 6 cases by Spreer et al and in 2 case reports by Nagasaka et al ( 6 , 21 ). Interestingly, ubiquitous mass-like contrast enhancement is not a typical finding of parenchymal hematomas, which rather show circumferential enhancement during organization and resorption ( 27 ). It is possible that mass-like contrast enhancement in cSDH is rather the result of contrast leakage via the inflammatory membranes into non-solid hematomas.…”
Section: Discussionmentioning
confidence: 99%
“…The intracapsular bleeding can show different degrees of T1 and T2 hyperintensity depending on its chronicity. According to other studies [ 9 , 10 ], the ring enhancement with intracapsular bleeding on MRI can be very helpful in the diagnosis of CEIH. Treatment is based on surgical removal of the mass.…”
Section: Introductionmentioning
confidence: 99%
“…In a retrospective review of five patients, Cai et al (2017) described CT and MRI characteristics of CEIH. On CT imaging, CEIH was reported as almost circular or elliptical cystic lesions surrounded by an enhancement such as brain abscesses [ 9 ]. Unfortunately, these findings are not sufficient to confirm a diagnosis of CEIH.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation